USING STORYTELLING FOR TEACHING VOCABULARY - Farizawati Farizawati (Universitas Syiah Kuala, 2016)
The objective of this study was to investigate the effect of using the Storytelling Technique for teaching vocabulary to fifth grade students at Primary School, SDN 1 Peukan Pidie, Sigli. An experimental design was used in this study and the data was collected through a test as the instrument. The population of this study was all the fifth grade students at SDN 1 Peukan Pidie, Sigli and two classes were taken as the sample, one as the experimental class and the other as the control. The experimental class was taught using the Storytelling Technique, whilst the control class was taught by memorizing words. A pre-test and a post-test were used to collect the data. The data was then analyzed using statistical processes. The results showed that the mean score of the post-test from the experimental class was significantly higher than that from the control class (77 65). Furthermore, the result of the t-test from the experimental class was higher than that from the control class (10.98 7.45). These results showed that the students taught using the Storytelling Technique achieved better scores than those taught by using the Memorizing Words Technique.